Longitudinal Study on the Prevalence of Macular Ischemia and Its Association with Visual Acuity After Pars Plana Vitrectomy for Rhegmatogenous Retinal Detachment - Younas, Nabila; Qureshi, Nadeem; Manzoor, Amna; Ahmed, Talia; Bukatari, Filzah; Shahid, Mahwish (Journal of Rawalpindi Medical College, 2026)
Objective: To determine the frequency of macular ischemia and compare visual acuity in patients with and without macular ischemia following pars plana vitrectomy for rhegmatogenous retinal detachment(RRD). Methods: This prospective study was done on 82 patients with an age range of 18–70 years with primary RRD at the Ophthalmology Department of Alshifa Trust Eye Hospital, Rawalpindi. Exclusion criteria included secondary RRD, prior vitreoretinal surgery, having macular disease, low-quality OCTA scans, amblyopia, and/or recurrent retinal detachment. Best-corrected visual acuity (BCVA) and slit-lamp examination were done. One month postoperatively, macular ischemia was evaluated using OCTA by measuring foveal avascular zone (FAZ) and vessel density (VD), alongside postoperative BCVA and macular thickness. Demographic data, OCTA metrics, and visual outcomes were systematically recorded. Results: Macular ischemia was observed in 36 participants (43.9%). The median age was 30 years, and 65% were male. Median BCVA improved from 0.51 (IQR 0.28–0.74) before surgery to 0.30 (0.18–0.53) after surgery. The FAZ increased from 0.10 mm² (0.07–0.24) to 0.18 mm² (0.14–0.32), and vessel density decreased from 34.5% to 28.0%, with all changes being statistically significant. In age-stratified analysis, participants aged 18–35 years showed significant improvement in BCVA and microvascular changes (all p<0.001), while those aged 36–70 years had significant changes in FAZ (p=0.009) and vessel density (p=0.03) but no significant improvement in BCVA (p=0.10) Conclusion: Macular ischemia is common after PPV for RRD. Though BCVA may improve postoperatively, minor retinal microvascular changes in the form of FAZ enlargement and reduced VD can persist. Keywords: Macular Ischemia; Tomography, Optical Coherence; Angiography; Retinal Detachment; Vitrectomy